2018
DOI: 10.1108/jiabr-06-2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

Do board characteristics affect bank performance? Evidence from the Bahrain Islamic banks

Abstract: Purpose Although most previous studies interested in Islamic banks have focused on quantitative aspects such as performance, risk and stability, this paper aims to deal with the institutional dimension and focus precisely on the link between board characteristics and bank performance. Design/methodology/approach Based on a data related to 13 banks in Bahrain observed over the period of 2005-2011, this study investigates the impact of board directors on the level of performance. To this end, the authors have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
96
6
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 65 publications
14
96
6
4
Order By: Relevance
“…The first study provides empirical evidence on the total SBB members, which is one of the measures used to explain the role of SSB, has a positive effect on profitability as measured by ROA Nomran, Haron, & Hassan, 2018;Farag, Mallin, & Ow-Yong, 2018;Mukhibad & Khafid, 2018). However, Hakimi, Rachdi, Mokni, and Hssini (2018); Ardana (2019); Grassa and Matoussi, (2014) also Mollah and Zaman (2015) stated that the total SBB members do not have a positive effect on ROA. Another indicator used to measure profitability is ROE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study provides empirical evidence on the total SBB members, which is one of the measures used to explain the role of SSB, has a positive effect on profitability as measured by ROA Nomran, Haron, & Hassan, 2018;Farag, Mallin, & Ow-Yong, 2018;Mukhibad & Khafid, 2018). However, Hakimi, Rachdi, Mokni, and Hssini (2018); Ardana (2019); Grassa and Matoussi, (2014) also Mollah and Zaman (2015) stated that the total SBB members do not have a positive effect on ROA. Another indicator used to measure profitability is ROE.…”
Section: Introductionmentioning
confidence: 99%
“…Another indicator used to measure profitability is ROE. According to Hakimi et al (2018); Grassa and Matoussi (2014) also Mollah and Zaman (2015), there are no relationships between the total SBB members with ROE. Furthermore, ; Nomran et al (2018); and Farag, Mallin, and Ow-Yong (2018) reported that the total SBB had a positive effect on ROE.…”
Section: Introductionmentioning
confidence: 99%
“…This chapter uses an unbalanced panel data of 66 IBs over 18 countries over the period 2007-2015 after eliminating banks with insufficient data on Shari'ah governance and performance. We choose the sample's starting period of 2007 in order to 2 Several variables relating to the SSB characteristics may determine how effective the SSB is in conducting its task, namely, SSB size, doctoral qualification, reputation, cross-membership and expertise [29,19,[30][31][32].…”
Section: Samplementioning
confidence: 99%
“…Dummy interaction is employed following literature[39] 4. To capture the crisis impact, dummy interaction is employed following literature, in which: "1" for the period 2007-2009, otherwise "0"[31].…”
mentioning
confidence: 99%
“…Shariah Committee (hereinafter referred to as "SC") plays a vital role by advising and supervising the operation of Islamic financial institutions in ensuring that the Islamic financial business carried out by Islamic financial institutions comply with the Shariah principles (Hidayat & Khalifa, 2018). SC is also considered as a key element (Hakimi, Rachdi, Mokni & Hssini, 2018) and the most crucial component in the governance framework of Islamic financial institutions (Grassa, 2013). The independence of the SC in discharging their duties and responsibilities is the essential element in ensuring the credibility of the institutions (Hassan, Othman, Salleh & Hussain, 2016).…”
Section: Introductionmentioning
confidence: 99%